Medical invalidation is associated with structural barriers in postacute immune mediated syndromes based on patient perspectives in Germany - Jad Saad; Jens Hensen; Corinna Bergelt; Seraina Petra Lerch (Scientific Reports, 2026)
Abstract Post-acute immune-mediated syndromes (PAIMS), including Long COVID/Post-COVID (LC/PC), Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS), and post-acute COVID-19 vaccination syndrome (PACVS), are characterized by persistent, multisystemic symptoms and significant healthcare challenges. A key issue is medical invalidation, defined as the dismissal or delegitimization of patients’ reports of symptoms. This cross-sectional online study, conducted in Germany between October and December 2025 ( N = 577), examined healthcare experiences, access barriers, and perceived invalidation. Although healthcare utilization was high, 87% of participants reported difficulties accessing appropriate treatment. Major barriers included lack of available therapies (60%) or not being taken seriously (26%). Perceived invalidation by medical personnel was moderate across all groups (LC: M = 2.80; ME/CFS: M = 2.99; PACVS: M = 3.03) and did not differ significantly (Welch-F(2, 190.50) = 2.87, p = 0.059) between groups. Invalidation occurred not only within healthcare settings but was particularly pronounced in interactions with authorities and workplaces. Social media and online communities served as important sources of information and support, especially among individuals with ME/CFS. Overall, the findings reveal substantial structural barriers in the care of PAIMS and highlight the need for improved clinical education, better care coordination, and stronger institutional recognition of these conditions.